PENGARUH RISIKO BISNIS, LIKUIDITAS, PERTUMBUHAN PENJUALAN DAN PERISAI PAJAK NON-UTANG TERHADAP STRUKTUR MODAL - Syafri Nosit; Yulia Efni; Gusnardi Gusnardi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study is aimed to examine the effect of risk business, liquidity, sales growth, non-debt tax shield on capital structure. The population of this study is metal and allied products companies listed in Indonesia Stock Exchange from 2014 - 2018. The sample of the study is all companies were selected by purposive sampling method. Based on the criteria, 13 companies were chosen as the samples of this study. This study used multiple linear regression analysis was used to test whether the independent variables affect the dependent variables. The results of this study is found that risk business and non-debt tax shield on capital structure have a negative an insignificant effect on capital structure, Liquidity and Sales Growth on capital structure have a negative an significant effect on capital structure. The limitations of this study are driven by the variable, year and sample size. Therefore further reseacrh can use other variables and extension other industries could bring the comprehensive results